Adrenocortical tumor with precocious puberty in a 2‐month‐old girl. Issue 5 (10th September 2015) - Marret, Jean‐Baptiste; Raffoul, Lara; Ribault, Virginie; Ravasse, Philippe; Rod, Julien
Abstract: Adrenocortical tumor is a rare childhood tumor with a median age at onset of 3.2 years. Virilization is the most common sign. Laparotomy is the reference treatment and has a favorable course. The diagnosis of adrenal tumor can be difficult. The main parameters of malignant tumors are size and metastasis. Analysis of TP53 mutation can facilitate final diagnosis. We report a case of virilizing adrenal tumor that developed in a 2‐month‐old girl, and which was treated with laparoscopic adrenalectomy.